SCIENTIFIC APPROACH: AN ENGLISH LEARNING-TEACHING (ELT) APPROACH IN THE 2013 CURRICULUM - Intan Siti Nugraha; Didi Suherdi (Journal of English and Education, 2017)
The primary focus of the study entitled Scientific Approach: An English Learning-Teaching (ELT) Approach In The 2013 Curriculum (A Descriptive Study of Teacher in One Junior High School in Bandung) is to investigate the practice of a teacher implementing scientific approach in English learning-teaching in one junior high school in Bandung and reveal the difficulties encountered by the teacher in the process. In particular, this study portrays the occurrence of activities and the quality of the teaching process through pedagogical microscope. This study employs a descriptive-qualitative research design. The data were procured from classroom observation, teacher’s lesson plan analysis and interview. Those data were analyzed by Pedagogical Microscope instrument (Suherdi, 2009). The findings show to some extents. First, the finding shows that all the five stages of scientific approach were completely executed in four meetings of delivering one material or one Basic Competence (KD) eventhough the five stages were not always conducted in every meeting which was different from lesson plan made. The teacher provided plenty activities in each stage. Scientific approach implemented by the teacher could engage students in active learning activities and develop various students’ contributions. The ways the teacher led the active learning activities and students’ contributions were varied depending on the stages. Scientific approach implemented successfully fostered students’ critical thinking and developed high-thinking level of students’ learning behaviour. Second, the difficulties encountered by the teacher during implementation were the problem on the students with low English proficiency, time allotment, and the teacher’s teaching management.